2014
DOI: 10.1177/0145561314093004-512
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Role of Single-Photon Emission Computed Tomography in the Assessment of Neurotologic Complaints

Abstract: We conducted a retrospective study to reexamine the value of singl e-photon emission computed tomography (SPECT) in the evaluation of patients with neurotologic complaints, and to assess the intra-and inter-radiologist variability ofSPECT readings. Ourstudypopulationwas made up of63 patients-23 men and 40 women, aged 34 to 91 years (mean: 59)-who had presented to a tertiary care otolaryngology practice and universit y hospital for evaluation of head trauma, sensorineural hearing loss, tinnitus, and/or vertigo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The review identified 52 cross-sectional studies and 19 longitudinal studies including a total of 2,634 individuals over 30 years of literature. In addition, seven studies which were not included in the systematic review contain 223 subjects ( 45 51 ). Subsequently, two large retrospective studies comparing SPECT neuroimaging in TBI, post-traumatic stress disorder (PTSD), and normals containing over 21,399 subjects have been published ( 52 , 53 ).…”
Section: Assessment Of the State Of The Art—spect In Brain Disordersmentioning
confidence: 99%
“…The review identified 52 cross-sectional studies and 19 longitudinal studies including a total of 2,634 individuals over 30 years of literature. In addition, seven studies which were not included in the systematic review contain 223 subjects ( 45 51 ). Subsequently, two large retrospective studies comparing SPECT neuroimaging in TBI, post-traumatic stress disorder (PTSD), and normals containing over 21,399 subjects have been published ( 52 , 53 ).…”
Section: Assessment Of the State Of The Art—spect In Brain Disordersmentioning
confidence: 99%